Prevention of ovarian hyperstimulation syndrome in a rat model: comparison of the efficacy of tocilizumab with that of ranibizumab, cabergoline, and a gonadotropin-releasing hormone antagonist. (2nd December 2015) - Taskin, Mine Islimye; Topcu, Onur; Yay, Arzu; Erken, Gulten; Balcioğlu, Esra; Adali, Ertan; Hismiogulları, Adnan Adil
Abstract: The aim of the study is to investigate the effects of the interleukin-6 (IL-6) blocker tocilizumab in a hyperstimulated rat model and compare it with ranibizumab, a gonadotropin-releasing hormone antagonist (GnRHA), and cabergoline. Forty-seven rats were randomly divided into the following seven groups: Group 1: OHS; Group 2: OHS+ GnRHA; Group 3: OHS + ranibizumab; Group 4: OHS + cabergoline; Group 5: OHS + low-dose tocilizumab (TL); Group 6: OHS + high-dose tocilizumab (TH); Group 7: sham. Ovarian weight was significantly lower only in the ranibizumab group than in the OHS group. Estrogen levels were significantly lower in the GnRHA group than in the OHS and the treatment groups. Progesterone levels were significantly lower in the ranibizumab, cabergoline, and TL groups than in the OHS group. Among the treatment groups, corpus luteum counts were lower than in the OHS group. Corpus luteum counts were lowest in the tocilizumab groups. IL-6 intensity was lower in all treatment groups than in the OHS group. In the ranibizumab group IL-6 intensity was the lowest. The TL group did not significantly differ from the GnRHA and cabergoline groups regarding IL-6 expression. Ovarian VEGF expression was significantly lower in all treatment groups. For the TL, ranibizumab, and cabergoline groups VEGF intensity was similar. Tocilizumab may be a new strategy for preventing ovarian hyperstimulation syndrome by inhibition of IL-6.